Analysis of Strategic Planning of Education at SMAN 1 Cisayong in Realising the Golden Generation of Indonesia - Khadijah, Ifah; Supianah, Iis; Agestiningsih, Veronika Sri; Patimah, Euis Guntur; Sultoni, Ilham Aziz (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This study aims to analyse the strategic planning of education at SMAN 1 Cisayong to realise the Golden Indonesia Generation. The focus of the analysis includes the synergy between the vision, mission, goals, and programmes of the school with the characteristics of the Golden Indonesia Generation, as well as the effectiveness of the implementation of strategic planning. The research participants included the principal, vice principal, teachers, and school committee at SMAN 1 Cisayong, which had a total of 30 people. The research method used was qualitative with a case study approach. Data collection was conducted through interviews, observations, and document studies. Data were analysed through data reduction, data presentation and conclusion-drawing techniques. The results showed that the strategic planning of education at SMAN 1 Cisayong is quite good. However, there are still some things that need to be improved, including the lack of student involvement in the preparation of strategic planning and the lack of comprehensive evaluation. This study concludes that the strategic planning of education at SMAN 1 Cisayong needs to be optimised to be more effective in realising the Golden Indonesia Generation. The implication of this research is the need for increased participation of all parties in the preparation and strategic planning, as well as improved monitoring and continuous evaluation.